From Conflict to Cohesion: Unveiling Ambon's Journey Through Collective Memory Analysis and Post-Conflict Reconciliation - Rachel Iwamony; Rolland Alexander Samson (UIN Sunan Gunung Djati Bandung, 2023)
This article delves into the religious conflict that transpired in Ambon from 1999 to 2004, with a specific focus on elucidating the formation of collective memory as a pivotal mechanism for fostering post-conflict reconciliation. Employing a methodology amalgamating literature review and in-depth interviews, this research scrutinizes the intricate dynamics of the conflict, delineating the roles played by both Muslim and Christian communities, not only as victims but also as perpetrators. The principal findings underscore the shared responsibility of both groups in instigating the conflict, resulting in egregious acts such as assaults, homicides, and property destruction. The article accentuates the imperative of mutual acknowledgment regarding each community's role in the conflict as an indispensable stride towards reconciliation. It posits that an accurate and all-encompassing collective memory of the conflict serves as a catalyst for communities to critically assess their religious practices and fosters a climate of receptivity to broader religious understandings. The research underscores the significance of cultivating a nuanced collective memory in upholding peace and harmony within a diverse post-conflict society.